Association between the group III metabotropic glutamate receptor gene polymorphisms and attention-deficit/hyperactivity disorder and functional exploration of risk loci. (January 2021) - Zhang, Qi; Chen, Xinzhen; Li, Shanyawen; Yao, Ting; Wu, Jing
Abstract: Existing evidence suggests that the group III metabotropic glutamate receptor (mGluR) gene variations are involved in attention-deficit/hyperactivity disorder (ADHD), but few studies have fully explored this association. We conducted a case-control study with 617 cases and 636 controls to investigate the association between functional single-nucleotide polymorphisms (SNPs) from the group III mGluR gene polymorphisms (GRM4, GRM7, GRM8) and ADHD in the Chinese Han population and initially explored the function of positive SNPs. The GRM4 rs1906953 T genotype showed a significant association with a decreased risk of ADHD (TT:CC, OR  = 0.55, 95% CI  = 0.40–0.77; recessive model, OR  = 0.58, 95% CI  = 0.43–0.78). GRM7 rs9826579 C showed a significant association with an increased risk of ADHD (TC:TT, OR = 1.81, 95% CI  = 1.39–2.36; dominant model, OR = 1.74, 95% CI  = 1.35–2.24; additive model, OR = 1.56, 95% CI  = 1.24–1.97). In addition, compared with subjects with the rs1906953 TT genotype, subjects with of the CC genotype showed more obvious attention deficit behaviours and hyperactivity/impulsive behaviours. Dual-luciferase reporter gene assays showed that a promoter reporter with the rs1906953 TT genotype significantly decreased luciferase activity compared with the CC genotype. According to electrophoretic mobility shift assays, the binding capacity of rs1906953 T probe with nucleoprotein was lower than that of the rs1906953 C probe. Our results revealed the association of GRM4 rs1906953 and GRM7 rs9826579 with ADHD. Moreover, we found that rs1906953 disturbs the transcriptional activity of GRM4. Highlights: GRM7 rs9826579 was associated with the risk of ADHD. GRM4 rs1906953 was involved in ADHD, and associated with inattention and hyperactivity. rs1906953 disturbed the transcriptional activity of GRM4.